Effects of iRGD conjugation density on the in vitro and in vivo properties of cylindrical polymer brushes. (17th May 2022) - Yin, Changfeng; Xiao, Panpan; Liang, Mengke; Li, Jia; Sun, Ying; Jiang, Xiqun; Wu, Wei
Abstract : Cylindrical polymer brushes with different iRGD conjugation densities were synthesized and iRGD density effects on their biological properties were obtained. Abstract : iRGD can significantly improve the tumor accumulation and tumor penetration of nanomaterials. However, it still remains unclear how far iRGD can enhance the properties of nanomaterials when its conjugation density is maximized. Herein, we synthesized three types of cylindrical polymer brushes (CPBs) with 0%, 50% and 100% of side chains terminated by iRGD, which were named CPBs-1, CPBs-2 and CPBs-3, respectively, and studied the effects of iRGD density on their cellular uptake, and tumor targeting ability and tumor permeability. It was demonstrated that compared with the iRGD-free CPBs-1, the cellular uptake of CPBs-3 was enhanced 5 times and their tumor accumulation was enhanced twice. The penetration depth of CPBs-3 in three-dimensional multicellular spheroids was larger than 100 μm. Our results provide useful information for the design of active tumor targeting nanomaterials as therapeutics or contrast agents.